Excitatory amino acid-stimulated uptake of 22Na+ in primary astrocyte cultures - Kimelberg, HK (J Neurosci, 1989)
In this study we have found that L-glutamic acid, as well as being taken up by a Na+-dependent mechanism, will stimulate the uptake of 22Na+ by primary astrocyte cultures from rat brain in the presence of ouabain. By simultaneously measuring the uptake of 22Na+ and L-3H- glutamate a stoichiometry of 2–3 Na+ per glutamate was measured, implying electrogenic uptake. Increasing the medium K+ concentration to depolarize the cells inhibited L-3H-glutamate uptake, while calculations of the energetics of the observed L-3H-glutamate accumulation also supported an electrogenic mechanism of at least 2 Na+:1 glutamate. In contrast, kinetic analysis of the Na+ dependence of L-3H-glutamate uptake indicated a stoichiometry of Na+ to glutamate of 1:1, but further analysis showed that the stoichiometry cannot be resolved by purely kinetic studies. Studies with glutamate analogs, however, showed that kainic acid was a very effective stimulant of 22Na+ uptake, but 3H-kainic acid showed no Na+ -dependent uptake. Furthermore, while L-3H-glutamate uptake was very sensitive to lowered temperatures, glutamate-stimulated 22Na+ uptake was relatively insensitive. These results indicate that glutamate-stimulated uptake of 22Na+ in primary astrocytes cultures cannot be explained solely by cotransport of Na+ with glutamate, and they suggest that direct kainic acid-type receptor induced stimulation of Na+ uptake also occurs. Since both receptor and uptake effects involve transport of Na+, accurate measurements of the Na+ :glutamate stoichiometry for uptake can only be done using completely specific inhibitors of these 2 systems.